2013
DOI: 10.1016/j.conbuildmat.2012.07.106
|View full text |Cite
|
Sign up to set email alerts
|

Damage monitoring in fibre reinforced mortar by combined digital image correlation and acoustic emission

Abstract: International audienceThe present work aims at developing a methodology for the detection and monitoring of damage and fractures in building materials in the prospects of energetic renovation. Digital image correlation (DIC) and acoustic emission (AE) monitoring were simultaneously performed during tensile loading tests of fibre reinforced mortar samples. The full-field displacement mappings obtained by DIC revealed all ranges of cracks, from microscopic to macroscopic, and an image processing procedure was co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
29
0
1

Year Published

2013
2013
2021
2021

Publication Types

Select...
5
2
2

Relationship

1
8

Authors

Journals

citations
Cited by 80 publications
(31 citation statements)
references
References 33 publications
1
29
0
1
Order By: Relevance
“…The metal bar/fiber reinforcement and the potential encapsulated healing agent/embedded agent network contribute to the material's heterogeneity. Still in literature the location of damage in sound specimens or structures has been detected with suitable engineering accuracy [16,17]. However, the damage development complicates the wave propagation on concrete and concrete composites [18,19], reducing the wave transmission and speed characteristics.…”
Section: Focus On the Acoustic Emission Technique: The Challenge Due mentioning
confidence: 99%
“…The metal bar/fiber reinforcement and the potential encapsulated healing agent/embedded agent network contribute to the material's heterogeneity. Still in literature the location of damage in sound specimens or structures has been detected with suitable engineering accuracy [16,17]. However, the damage development complicates the wave propagation on concrete and concrete composites [18,19], reducing the wave transmission and speed characteristics.…”
Section: Focus On the Acoustic Emission Technique: The Challenge Due mentioning
confidence: 99%
“…The AE energy, which is proportional to the released energy at the fracture incidents, has been used in damage characterization in similar studies [7,8]. In order to illustrate the relationship between AE results and the mechanical properties, a typical case of load and AE energy with time were plotted in Figure 4.…”
Section: A Crack Development and Classificationmentioning
confidence: 99%
“…Fracture positions and sizes can either come from a manual input or from experimental measurements: in a previous work, digital image correlation was used during the mechanical loading of concrete samples. This technique provides two-dimensional displacement mappings, from which crack networks could be derived following an appropriate image processing methodology [28]. The result of this procedure is the quantification of all visible cracks in the form of a distributed set of segments of known aperture.…”
Section: Flow In Fractured Porous Media 221 Fracture Integrationmentioning
confidence: 99%
“…A mixed approach is followed to this aim, using experimental measurements of crack patterns as an input for a numerical model for coupled heat and moisture flow. In a recent study [28], digital image correlation and acoustic emission monitoring were found reliable for the quantification and localisation of all scales of fissures, from micro-cracks to macroscopic fractures. A numerical code was then developed [31], that may include these measurements into a finite-element frame for the prediction of coupled heat and moisture flow.…”
Section: Introductionmentioning
confidence: 99%